Effectiveness of Interval Versus Continuous Training on Blood Pressure Among Hypertensive Postmenopausal Women (International Journal of Physiotherapy, 2025)
Background: Hypertension is a significant risk factor for cardiovascular disease (CVD) in postmenopausal women. The decline in estrogen levels during menopause contributes to increased oxidative stress, endothelial dysfunction, and heightened sympathetic activity, all of which can elevate blood pressure. Various approaches, including pharmacological and nonpharmacological interventions, are utilized to manage hypertension, with aerobic exercise being a recommended strategy for both prevention and treatment. However, limited research directly compares the effects of interval and continuous aerobic training on blood pressure in hypertensive postmenopausal women. This study aimed to assess the effectiveness of moderateintensity continuous aerobic training and high-intensity interval aerobic training in reducing blood pressure and body mass index (BMI) in this population.Methods: This experimental study included 30 postmenopausal women diagnosed with Stage 1 hypertension, randomly assigned to three groups: Group A (moderate-intensity continuous aerobic training), Group B (high-intensity interval aerobic training), and Group C (control group). The intervention lasted six weeks, with training sessions conducted thrice weekly.Blood pressure and BMI were recorded before and after the intervention. Data analysis involved ANOVA and post-hoc tests to examine intra-group and inter-group differences.Results: Both Group A and Group B showed a significant reduction in systolic and diastolic blood pressure (p